2012
DOI: 10.3340/jkns.2012.51.6.359
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surgery Time on Prognosis in Newborns with Meningomyelocele

Abstract: ObjectiveTo investigate the effect of surgery time on prognosis of newborns with meningomyelocele.MethodsThe records of neonates with meningomyelocele were retrospectively analyzed. Demographic and clinical characteristics as well as information, timing of surgery, and durations of hospital stay and antibiotic therapy were recorded.ResultsThe records of 30 babies were included in the final analysis. Overall, the mean gestational age was 37.7±2.7 weeks, with a mean birth weight of 2967±755 g and head circumfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
2
18
3
1
Order By: Relevance
“…Spatial and temporal access is chiefly important because the lack of medical resources reduces the accessibility of residents’ access to neurosurgical care. In particular, the accessibility of neurosurgeons in neurosurgical emergencies, such as trauma or vascular, is of utmost importance 12) . The aim of this study is to assess the actual geometrical distribution of neurosurgeons across Korea and to identify possible problem that may arise from such distribution trait.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial and temporal access is chiefly important because the lack of medical resources reduces the accessibility of residents’ access to neurosurgical care. In particular, the accessibility of neurosurgeons in neurosurgical emergencies, such as trauma or vascular, is of utmost importance 12) . The aim of this study is to assess the actual geometrical distribution of neurosurgeons across Korea and to identify possible problem that may arise from such distribution trait.…”
Section: Introductionmentioning
confidence: 99%
“…The current approach to the timing of MMC surgical repair is in favor of early surgery [14,15]. However, it is necessary to have an appropriate time interval to obtain comprehensive information about the patient's clinical condition and to plan surgical reconstruction adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Early aggressive treatment approach in postnatal MMC surgery reduces early morbidity and mortality rates [32]. Oncel et al demonstrated that early surgery (<5 days) shortened hospital stay and antibiotic treatment time and reduced complication rates [14]. In the long term, it is reported that cognitive functions are better, need for long-term care and incidence of urinary incontinence are reduced and it positively affects neurogenic bladder prognosis and thus urinary tract function [33,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Sac repair is suggested to be performed in the first 36 hours; some studies have suggested that a shunt should be placed in a second operation, while some studies have demonstrated that the risk of ventriculitis and shunt infection decreases in cases in which sac repair and VP shunt placement is performed in the same operation (2,7,8). We considered that the best option is to decide according to the condition of the patient and the circumstances.…”
Section: Case Presentationmentioning
confidence: 99%